2007
DOI: 10.1007/s00420-007-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prevention of needlestick injuries among health care workers in a German university hospital

Abstract: There is a high rate of needlestick injuries in the daily routine of a hospital. The rate of such injuries depends on the medical discipline. Implementation of safety devices will lead to an improvement in medical staff's health and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
113
10
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 27 publications
14
113
10
9
Order By: Relevance
“…The studies from Alexandria hospital [16] Egypt (67.9%), a study from Nigeria [17] involving primary health care workers (57.1%) and a study from Pakistan [18] involving health care workers of two tertiary care hospitals comprising both public and private health sector (64%) have shown marginally lower percentage of needle stick injuries in relation to the present study observation. In contrast to the present study findings, studies from Germany [3,19] Maharashtra-India [13] and Mongolia [20,21] have shown significant lower proportion of needle stick injuries i.e. 31.5%, 49.1% and 38.4% respectively among the health care personnel.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The studies from Alexandria hospital [16] Egypt (67.9%), a study from Nigeria [17] involving primary health care workers (57.1%) and a study from Pakistan [18] involving health care workers of two tertiary care hospitals comprising both public and private health sector (64%) have shown marginally lower percentage of needle stick injuries in relation to the present study observation. In contrast to the present study findings, studies from Germany [3,19] Maharashtra-India [13] and Mongolia [20,21] have shown significant lower proportion of needle stick injuries i.e. 31.5%, 49.1% and 38.4% respectively among the health care personnel.…”
Section: Discussioncontrasting
confidence: 99%
“…Health care personnel are at increased risk of contracting blood borne pathogens due to their occupational exposure to blood and body fluids [1][2][3][4]. More than twenty diseases can get transmitted through needle stick injuries including Hepatitis B, Hepatitis C and HIV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on NSI and sharp injuries among health care workers have been reported from all over the world. [1][2][3]5,[7][8][9][11][12][13] In the present study, around 40% of the HCWs reported having received NSI in their carrier, which is a concerning number. Few of the studies in North India had found a high prevalence of NSI (79.5% and 73%, which is higher as compared to the present study.…”
Section: Discussionmentioning
confidence: 75%
“…In a similar study by Wicker et al among healthcare professionals of a German university hospital, 31.4% of all workers admitted that they had been subject to exposure and the percentage was higher among physicians -55.1% than among nurses -22.0%. Most exposures occurred in the employees of surgical wards -46.9% of cases (69.5% of doctors and 31.4% of nurses) [13].…”
Section: Ijomeh 2014;27(5) 754mentioning
confidence: 99%